2015
DOI: 10.1002/rra.2972
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Between One-Dimensional and Two-Dimensional Hydrodynamic Models for Ecohydraulic Analysis

Abstract: 14Aquatic habitat assessment and river restoration design require geospatially explicit maps of 15 hydraulic conditions. Diverse mechanistic ecohydraulic models compute spatially explicit depth 16and velocity results to evaluate habitat suitability spatially as a function of these abiotic 17conditions. This study compared depth and velocity results from two-dimensional (2D) and one-18 dimensional (1D) hydraulic models with algorithms that laterally discretize 1D velocity and 19 interpolate depth and velocity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 52 publications
(89 reference statements)
3
18
0
Order By: Relevance
“…To exemplify data resolution, within and beyond the wetted area at 24.92 m 3 /s, overall point density downstream of the Highway 20 Bridge was 59 and 554 points per 100 m 2 , respectively. As previously published in 10 journal articles (e.g., Gibson & Pasternack, ; Gonzalez & Pasternack, ; Wyrick & Pasternack, ), SRH‐2D (v. 2.1) was used to simulate meter‐scale, nonvegetated, in‐channel river hydraulics in the LYR from 8.50 to 3,126 m 3 /s (0.06 to 22 times bankfull discharge).…”
Section: Methodsmentioning
confidence: 99%
“…To exemplify data resolution, within and beyond the wetted area at 24.92 m 3 /s, overall point density downstream of the Highway 20 Bridge was 59 and 554 points per 100 m 2 , respectively. As previously published in 10 journal articles (e.g., Gibson & Pasternack, ; Gonzalez & Pasternack, ; Wyrick & Pasternack, ), SRH‐2D (v. 2.1) was used to simulate meter‐scale, nonvegetated, in‐channel river hydraulics in the LYR from 8.50 to 3,126 m 3 /s (0.06 to 22 times bankfull discharge).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is important to know the impact of the hydromorphological characteristics of the stream on the aquatic ecosystem [3,4]. Abiotic characteristics, together with habitat quality, form the basis for assessing the habitat availability [5,6]. The set of these relationships is the basis for a comprehensive environmental assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Manning's equation used in this study is widely accepted methodology in stream resistance evaluation, especially in vegetated areas [46], and was successfully incorporated in numerous researches investigating the impact of vegetation on water flow, depth and velocity [32,33,47,48]. A quantitative comparison of calibrated Manning's coefficient values with those reported in the literature can be made, linking plant traits (height and flexibility) to roughness.…”
Section: Discussionmentioning
confidence: 91%
“…Here, the MFRM is optimized using actual measured entry discharge into each single channel of the complex anastomosing system, which is a significant advantage of this study. Gibson and Pasternack [33] developed a 1D model for anastomosing reach of the River Yuba where only one bifurcation was modeled. With no measurements on discharge division between the channels, the authors found 1D model simulations underwhelming and split flow modeling to be complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation